1995
DOI: 10.1002/jbm.820290309
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative biodegradation mechanisms of biaxially strained poly(etherurethane urea) elastomers

Abstract: As part of ongoing studies in polyurethane biostability and biodegradation, we have investigated an in vitro system to test strained poly(etherurethane urea) (PEUU). Recently, we utilized this system to reproduce in vivo stress cracking in strained Pellethane. In this study, strained PEUU was tested to determine whether it degrades through a common mechanism with Pellethane and to further examine the steps involved in this degradation. Biaxially strained PEUU elastomers were treated with an alpha 2-macroglobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
138
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(155 citation statements)
references
References 16 publications
17
138
0
Order By: Relevance
“…81,82 This normal host response causes soft segment chain scission and aberrant crosslinking of the polyether or polycarbonate soft segments, which is then grossly observed as surface cracking of the poly(ether urethane) components of the cardiovascular device. [83][84][85] Microscopic evidence of surface degradation has been observed by others and us to be present as early as 90 days post implantation. [83][84][85][86] With respect to pacemaker leads, which commonly use polyurethane insulation, the duration from implantation to device failure has been shown to be as short as $2.5 years.…”
Section: Cd47-modified Polymerssupporting
confidence: 70%
“…81,82 This normal host response causes soft segment chain scission and aberrant crosslinking of the polyether or polycarbonate soft segments, which is then grossly observed as surface cracking of the poly(ether urethane) components of the cardiovascular device. [83][84][85] Microscopic evidence of surface degradation has been observed by others and us to be present as early as 90 days post implantation. [83][84][85][86] With respect to pacemaker leads, which commonly use polyurethane insulation, the duration from implantation to device failure has been shown to be as short as $2.5 years.…”
Section: Cd47-modified Polymerssupporting
confidence: 70%
“…It has been shown that biodegradation can be monitored in polyether polyurethanes by peak height analysis of the peaks associated with ether, methylene, and urethane linkages. 3 Other bands that show changes due to biodegradation are: 1367 cm −1 , (CH 2 ) from the ␣-carbon of the PTMG; 1709 cm −1 , hydrogen-bonded urethane carbonyl; and 1730 cm −1 , nonhydrogen-bonded urethane carbonyl. The 1174 cm −1 band is attributed to degradation products in the polyether polyurethanes, and this band has been assigned to a branched ether created by crosslinking of the soft segment.…”
Section: Attenuated Total Reflectance-fourier Transform Infrared Specmentioning
confidence: 98%
“…The 1174 cm −1 band is attributed to degradation products in the polyether polyurethanes, and this band has been assigned to a branched ether created by crosslinking of the soft segment. 3 Since SPU-S is a polyether polyurethane with polydimethylsiloxane endcaps, the 1260 cm −1 (C−H of Si−CH 3 ) and 800 cm −1 (Si−C) also were examined for any changes. 19 Peak height analysis on SPU-C and SPU-PCU, with the polycarbonate soft segment, was done on the 1740 cm −1 (C=O) band associated with the carbonate linkage.…”
Section: Attenuated Total Reflectance-fourier Transform Infrared Specmentioning
confidence: 99%
See 1 more Smart Citation
“…This is 303 adequately covered in literature (Stokes et al, 1995;Wiggins et al, 2003;Thoma, 1987;Schmidt et 304 al., 1998;Zhao et al, 1990Zhao et al, , 1991Wu et al, 1992;Schubert et al, 1995Schubert et al, , 1997 …”
mentioning
confidence: 99%